Current and historical patterns of recruitment of Yellowstone cutthroat trout in Yellowstone Lake, Wyoming, as revealed by otolith microchemistry - Kole P. Stewart; Thomas E. McMahon; Todd M. Koel; Robert Humston (Hydrobiologia, 2024)
Yellowstone cutthroat trout inhabiting Yellowstone Lake have declined substantially over the past 25 years as a result of predation by invasive lake trout, the presence of whirling disease, and periods of persistent drought. We used otolith microchemistry to assess whether cutthroat trout recruitment patterns have changed in response to these environmental stressors. Though water chemistry variation among the 22 sampled spawning tributaries was low, we identified 9 distinct spawning stream clusters. Random forest models were developed for assessing relative recruitment, yielding a high classification accuracy of 84.4% for known-origin cutthroat trout fry otoliths and 79.0% for simulated otolith signatures based on water chemistry. Proportion of recruitment varied significantly between pre- and post-stressor samples (X 2 = 15.40, P = 0.03). The majority of pre- (0.84) and post-stressor (0.77) recruitment occurred in the same three stream clusters, but there was a notable decrease in recruitment in streams with high whirling disease prevalence, and a notable increase from the tributary cluster without whirling disease and with low lake trout predation risk. Conservation efforts should be focused on protecting important spawning tributaries and improving cutthroat trout recruitment in spawning streams that in the past likely contributed much greater numbers of fish.

Modeling the Distribution of Atlantic Croaker and Spot in a Dynamic Seascape Using Metabolic Scope - Benjamin J. Marcek; Robert Humston; Mary C. Fabrizio; Jian Shen; Richard W. Brill (Estuaries and Coasts, 2024)
In estuarine and coastal systems, anthropogenic activities and directional changes in global air temperatures have led to increased water temperatures, as well as increased frequency and severity of episodic hypoxia. These alterations have had population-level effects on aquatic organisms, including changes in species-specific distributions. Because physiology is the transfer function connecting environmental conditions to individual behaviors and eventually to population-level effects, we used individual-based models (IBMs) that incorporate changes in metabolic scope as motivation for movement. Our objective was to investigate the effects of temperature and hypoxia on the distribution of Atlantic croaker and spot in Chesapeake Bay. We compared the predicted monthly fish distributions from the IBMs with apparent fish distributions recorded by the VIMS Juvenile Fish Trawl Survey during 1988–2014. IBMs failed to reproduce accurately the apparent spatial distributions of Atlantic croaker and spot. More specifically, compared with the trawl survey, IBMs predicted larger proportions of these two species would be captured in the lower regions of Chesapeake Bay and smaller proportions in the York and Rappahannock rivers. We postulate that, because similar thermal and oxygen conditions were occupied by fish in the IBMs and in the wild, temperature may not be the most important factor motivating the movement of Atlantic croaker and spot in Chesapeake Bay, and other spatial factors (e.g., prey availability) act in concert with temperature and hypoxia to determine the spatial distributions of Atlantic croaker and spot in Chesapeake Bay. Alternatively, surveys used to estimate species occurrences could be biased if gear vulnerability is affected by temperature or oxygen conditions (or both). Additional research is needed to clarify which condition is true or if a combination of these factors (and others) led to discrepancies between predicted and apparent fish distributions based on trawl survey data.

Use of otolith microchemistry to identify subbasin natal origin and use by invasive Lake Trout in Yellowstone Lake - Kole P. Stewart; Thomas E. McMahon; Todd M. Koel; Robert Humston (Hydrobiologia, 2021)

Migrations and movements of Atlantic tarpon revealed by two decades of satellite tagging - Jiangang Luo; Jerald S. Ault; Bruce T. Ungar; Steven G. Smith; Michael F. Larkin; Thomas N. Davidson; David R. Bryan; Nicholas A. Farmer; Scott A. Holt; A. Scott Alford; Aaron J. Adams; Robert Humston; et al. (Fish and Fisheries, 2020)
Understanding large‐scale migratory behaviours, local movement patterns and population connectivity are critical to determining the natural processes and anthropogenic stressors that influence population dynamics and for developing effective conservation plans. Atlantic tarpon occur over a broad geographic range in the Atlantic Ocean where they support valuable subsistence, commercial and recreational fisheries. From 2001 through 2018, we deployed 292 satellite telemetry tags on Atlantic tarpon in coastal waters off three continents to document: (a) seasonal migrations and regional population connectivity; (b) freshwater and estuarine habitat utilization; (c) spawning locations; and (d) shark predation across the south‐eastern United States, Gulf of Mexico and northern Caribbean Sea. These results showed that some mature tarpon make long seasonal migrations over thousands of kilometres crossing state and national jurisdictional borders. Others showed more local movements and habitat use. The tag data also revealed potential spawning locations consistent with those inferred in other studies from observations of early life stage tarpon leptocephalus larvae. Our analyses indicated that shark predation mortality on released tarpon is higher than previously estimated, especially at ocean passes, river mouths and inlets to bays. To date, there has been no formal stock assessment of Atlantic tarpon, and regional fishery management plans do not exist. Our findings will provide critical input to these important efforts and assist the multinational community in the development of a stock‐wide management information system to support informed decision‐making for sustaining Atlantic tarpon fisheries.

Age and intraspecific diversity of resilient Acropora communities in Belize - Adele Irwin; Lisa Greer; Robert Humston; Meghann Devlin-Durante; Paul Cabe; Halard Lescinsky; Karl Wirth; H. Allen Curran; Iliana B. Baums (Coral Reefs, 2017)

An initial assessment of drought sensitivity in Amazonian fish communities - Carlos E. C. Freitas; Flávia K. Siqueira-Souza; Robert Humston; Lawrence E. Hurd (Hydrobiologia, 2013)

Schooling and migration of large pelagic fishes relative to environmental cues - Robert Humston; Jerald S. Ault; Molly Lutcavage; Donald B. Olson (Fisheries Oceanography, 2000)
A kinesis model driven by high‐resolution sea surface temperature maps is used to simulate Atlantic bluefin tuna movements in the Gulf of Maine during summer months. Simulations showed that individuals concentrated in areas of thermal preference. Results are compared to empirical distribution maps of bluefin tuna schools determined from aerial overflights of the stock during the same time periods. Simulations and empirical observations showed similar bluefin tuna distributions along fronts, although interannual variations in temperature ranges occupied suggest that additional foraging factors are involved. Performance of the model is further tested by simulating the relatively large‐scale annual north–south migrations of bluefin tuna that followed a preferred thermal regime. Despite the model’s relatively simple structure, results suggest that kinesis is an effective mechanism for describing movements of large pelagic fish in the expansive ocean environment.